Adolescent transitions in reflexive and non-reflexive behavior: Review of fear conditioning and impulse control in rodent models. (November 2016) - Hunt, Pamela S.; Burk, Joshua A.; Barnet, Robert C.
Highlights: Fear conditioning during adolescence is greater than at other ages. Adolescent rodents show exaggerated fear and less fear extinction. Adolescent rodents are more impulsive and choose riskier options. Conditioning and decision making reveal nonlinear features during adolescence. Abstract: Adolescence is a time of critical brain changes that pave the way for adult learning processes. However, the extent to which learning in adolescence is best characterized as a transitional linear progression from childhood to adulthood, or represents a period that differs from earlier and later developmental stages, remains unclear. Here we examine behavioral literature on associative fear conditioning and complex choice behavior with rodent models. Many aspects of fear conditioning are intact by adolescence and do not differ from adult patterns. Sufficient evidence, however, suggests that adolescent learning cannot be characterized simply as an immature precursor to adulthood. Across different paradigms assessing choice behavior, literature suggests that adolescent animals typically display more impulsive patterns of responding compared to adults. The extent to which the development of basic conditioning processes serves as a scaffold for later adult decision making is an additional research area that is important for theory, but also has widespread applications for numerous psychological conditions.